Kesadaran Gen Z terhadap Dinamika Sosial-Politik di Indonesia: Perspektif Teori Ashabiyyah Ibnu Khaldun - Hannanda Harriyani (UIN Sunan Kalijaga Yogyakarta, 2024)
This article analyzes the political consciousness of Indonesia’s Generation Z (Gen Z) within the context of digital socio-political dynamics by employing Ibn Khaldun’s theory of ashabiyyah (social solidarity). Gen Z, defined as the digital-native cohort born between 1997 and 2012, exhibits unconventional and digitized patterns of political participation, primarily through social media platforms such as Instagram, X (Twitter), and TikTok. This study adopts a qualitative approach involving textual analysis and literature review of scholarly works, digital content, and survey reports. The findings indicate that the ashabiyyah of Gen Z no longer rests upon primordial ties but rather on digital solidarities that are temporary and project-based. From Ibn Khaldun’s perspective, such solidarities represent a new form of ashabiyyah that plays a significant role in shaping socio-political power. This study offers a reinterpretation of the classical ashabiyyah theory in the context of digital-generation politics and highlights the importance of value-based social cohesion in strengthening political participation and democracy amid the information disruption era. The article contributes to the advancement of Islamic political theory and generational studies within Indonesia’s contemporary political landscape. Abstrak Artikel ini menganalisis kesadaran politik Generasi Z (Gen Z) Indonesia dalam konteks dinamika sosial-politik digital dengan menggunakan teori ashabiyyah (solidaritas sosial) Ibnu Khaldun. Gen Z, sebagai generasi digital yang lahir antara tahun 1997 hingga 2012, menunjukkan pola partisipasi politik yang tidak konvensional dan terdigitalisasi, terutama melalui media sosial seperti Instagram, X (Twitter), dan TikTok. Penelitian ini menggunakan pendekatan kualitatif dengan analisis teks dan studi pustaka terhadap literatur, konten digital, serta laporan survei. Temuan menunjukkan bahwa ashabiyyah Gen Z tidak lagi berbasis pada ikatan primordial, melainkan pada solidaritas digital yang bersifat temporer dan berbasis proyek. Dalam perspektif Ibnu Khaldun, solidaritas semacam ini mencerminkan bentuk ashabiyyah baru yang berperan dalam pembentukan kekuatan sosial-politik. Studi ini menawarkan pembacaan ulang atas teori klasik ashabiyyah dalam konteks politik generasi digital, serta menyoroti pentingnya kohesi sosial berbasis nilai dalam memperkuat partisipasi politik dan demokrasi di era disrupsi informasi. Artikel ini berkontribusi pada pengembangan teori politik Islam dan studi generasi dalam lanskap politik kontemporer Indonesia